2021
DOI: 10.1002/ajpa.24464
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of hormonal modulation in mantled howler monkey males,Alouatta palliata

Abstract: Objectives: The study of hormone modulation may offer important insight into the responses of individuals to environmental challenges. Here we studied C-peptide, thyroid hormone (T3), glucocorticoid (GC), and testosterone (T) metabolites of mantled howler males to assess: 1) correlations among hormones; 2) individual and temporal variation in hormone concentrations; and 3) the influence of ecological, climatic, behavioral, social, and reproductive factors on hormone variation.Methods: We studied 10 adult males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…Using fecal T3 data, supporting comparative evidence is now available from several species of NHPs (Chen et al, 2021;Gesquiere et al, 2018;Thompson et al, 2017). Interestingly, this research and other work with NHPs (Dias et al, 2021) also demonstrates a positive relationship between fecal T3 levels and male mating effort, a finding that provides comparative evidence for influence of T3 on energy allocation specifically to male reproduction.…”
Section: Triiodothyronine (T3)supporting
confidence: 77%
“…Using fecal T3 data, supporting comparative evidence is now available from several species of NHPs (Chen et al, 2021;Gesquiere et al, 2018;Thompson et al, 2017). Interestingly, this research and other work with NHPs (Dias et al, 2021) also demonstrates a positive relationship between fecal T3 levels and male mating effort, a finding that provides comparative evidence for influence of T3 on energy allocation specifically to male reproduction.…”
Section: Triiodothyronine (T3)supporting
confidence: 77%
“…After the end of the playback experiments, we followed groups for the rest of the day. If before, during, or after the experiments we observed any of the following events, which are stimuli with the potential to affect mantled howler monkey behavior and physiology, we discarded the experiment and rescheduled it: aggression (Dias et al, 2017; n = 1 experiment); noise produced by aerial traffic, human voice (not produced by researchers), and tools/machinery (e.g., chainsaw, lawnmower: Gómez‐Espinosa et al, 2022; n = 8 experiments); mating (Dias et al, 2022; n = 1 experiment). All experiments were conducted under similar environmental conditions: no rain, absent to gentle wind (Beaufort Scale categories 0−2), mean SPL of 40.1 ± 2.1 dB.…”
Section: Methodsmentioning
confidence: 99%
“…Glucocorticoid hormones are released by the hypothalamo-pituitaryadrenocortical axis in response to psychological and energetic demands (Sapolsky et al, 2000). We have previously demonstrated that the fecal concentrations of glucocorticoid metabolites (fGCM) of mantled howler monkeys are responsive to social, ecological, and anthropogenic challenges (e.g., Cañadas-Santiago et al, 2020;Dias et al, 2017Dias et al, , 2022Gómez-Espinosa et al, 2014). Furthermore, there is a ca.…”
Section: Hormonal Samplingmentioning
confidence: 99%